Regulation of aspartate aminotransferase isoenzymes by hydrocortisone in the liver of aging rats - Sharma R.; Patnaik S.K. (My University, 2025)
The activities and induction patterns of the isoenzymes of aspartate aminotransferase of the liver of male rats of various ages were studied. The activity of cytoplasmic aspartate aminotransferase increases gradually till adulthood and remains constant thereafter with increasing age of the rat. However, the activity of mitochondrial isoenzyme remains constant throughout the life span of the rat. Adrenalectomy decreases and hydrocortisone increases the activity of cytoplasmic isoenzyme in rats of all ages. In contrast, the above treatments do not shown any affect on the activity of mitochondrial isoenzyme in the liver of rats of all ages. © 1987.